THE EFFECT OF ROSELLE (Hibiscus sabdariffa L.) PETALS EXTRACT AS ALTERNATIVE DISCLOSING SOLUTION FOR DENTAL PLAQUE IDENTIFICATION - Indah Dwi Febriyanti; Ike Dewi Liana; Risma Indriyani; Sandy Christiono (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Roselle (Hibiscus sabdariffa L.) is a plant with many functions, such as natural dyes. In dental health, disclosing agents are being used to identify the amounts of dental plaque by showing contrast colour of dental plaque. One of disclosing agent which often being used is disclosing solution. Purpose: To know the effect of roselle petals as alternative substitute disclosing solution to identify dental plaque with contrast color of plaque. Method: Research design was Quasi Experimental with Post Test Only Control Group Design. Subject was 45 people which divided into 3 groups. Group 1 was 15 people given roselle petals extract concentration 50%, Group 2 was 15 people given roselle petals extract concentration 100% and group 3 (control) was 15 people given disclosing solution. Result: The study results showed that the mean of plaque index after application of roselle petals extract concentration 50%, 100% and disclosing solution was 1,720, 1,951, 2,140. The data was tested using One Way ANOVA which was resulted in 0,018 significancy (p<0,05). There was significant differences of plaque index after three groups of application. Conclusion: There is significant effect of roselle petals extract concentration 100% as an alternative disclosing solution to determine dental plaque.Background: Roselle (Hibiscus sabdariffa L.) is a plant with many functions, such as natural dyes. In dental health, disclosing agents are being used to identify the amounts of dental plaque by showing contrast colour of dental plaque. One of disclosing agent which often being used is disclosing solution. Purpose: To know the effect of roselle petals as alternative substitute disclosing solution to identify dental plaque with contrast color of plaque. Method: Research design was Quasi Experimental with Post Test Only Control Group Design. Subject was 45 people which divided into 3 groups. Group 1 was 15 people given roselle petals extract concentration 50%, Group 2 was 15 people given roselle petals extract concentration 100% and group 3 (control) was 15 people given disclosing solution. Result: The study results showed that the mean of plaque index after application of roselle petals extract concentration 50%, 100% and disclosing solution was 1,720, 1,951, 2,140. The data was tested using One Way ANOVA which was resulted in 0,018 significancy (p<0,05). There was significant differences of plaque index after three groups of application. Conclusion: There is significant effect of roselle petals extract concentration 100% as an alternative disclosing solution to determine dental plaque. Keywords : Dental Plaque, Disclo